Review of artificial intelligence in smart wearable devices under internet of things communication - Minh Long Hoang; Guido Matrella; Paolo Ciampolini (IAES International Journal of Artificial Intelligence (IJ-AI), 2026)
This paper aims to provide a review about the role of artificial intelligence (AI) in wearable devices, specifically smartwatches, fitness trackers, smart clothes, and smart eyewear. Machine learning (ML) and deep learning (DL) play essential roles in the development of these devices, thanks to their advanced algorithms with the support of the internet of things (IoT) framework. AI functionalities and metrology are detailed in these wearables, highlighting the use of convolutional neural networks (CNN) and recurrent neural networks (RNN) for applications such as activity recognition, health monitoring, and personalized recommendations. The paper demonstrates the AI implementation in smart devices, including stress detection by heart rate variability (HRV), personalizing fitness recommendations, muscle activity monitoring, and real-time image recognition. Challenges and potential solutions are discussed for a deep comprehension of the AI development in wearable devices.